Everyday Ethics: Framing youth participation in organizational practice - Driskell, David; Kudva, Neema (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
Much of the literature on ethical issues in child and youth participation has drawn on the episodic experiences of participatory research efforts in which young people’s input has been sought, transcribed and represented. This literature focuses in particular on the power dynamics and ethical dilemmas embedded in time-bound adult/child and outsider/insider relationships. While we agree that these issues are crucial and in need of further examination, it is equally important to examine the ethical issues embedded within the “everyday” practices of the organizations in and through which young people’s participation in community research and development often occurs (e.g., community-based organizations, schools and municipal agencies). Drawing on experience from three summers of work in promoting youth participation in adult-led organizations of varying purpose, scale and structure, a framework is postulated that presents participation as a spatial practice shaped by five overlapping dimensions. The framework is offered as a point of discussion and a potential tool for analysis in examining ethical issues for young people’s participation in relation to organizational practice.